Perspectives in business informatics research : 17th International Conference, BIR 2018, Stockholm, Sweden, September 24-26, 2018, Proceedings /: 17th International Conference, BIR 2018, Stockholm, Sweden, September 24-26, 2018, Proceedings. (2018) - Unknown
No abstract available